Pathophysiological Consequences of KATP Channel Overactivity and Pharmacological Response to Glibenclamide in Skeletal Muscle of a Murine Model of Cantù Syndrome - Scala, Rosa; Maqoud, Fatima; Zizzo, Nicola; Mele, Antonietta; Camerino, Giulia Maria; Zito, Francesco Alfredo; Ranieri, Girolamo; McClenaghan, Conor; Harter, Theresa M.; Nichols, Colin G.; Tricarico, Domenico (Frontiers in Pharmacology, 2020)
Cantù syndrome (CS) arises from mutations in ABCC9 and KCNJ8 genes that lead to gain of function (GOF) of ATP-sensitive potassium (KATP) channels containing SUR2A and Kir6.1 subunits, respectively, of KATP channels. Pathological consequences of CS have been reported for cardiac and smooth muscle cells but consequences in skeletal muscle are unknown. Children with CS show muscle hypotonia and adult manifest fatigability. We analyzed muscle properties of Kir6.1[V65M] CS mice, by measurements of forelimb strength and ultrasonography of hind-limb muscles, as well as assessing KATP channel properties in native Flexor digitorum brevis (FDB) and Soleus (SOL) fibers by the patch-clamp technique in parallel with histopathological, immunohistochemical and Polymerase Chain Reaction (PCR) analysis. Forelimb strength was lower in Kir6.1wt/VM mice than in WT mice. Also, a significant enhancement of echodensity was observed in hind-limb muscles of Kir6.1wt/VM mice relative to WT, suggesting the presence of fibrous tissue. There was a higher KATP channel current amplitude in Kir6.1wt/VM FDB fibers relative to WT and a reduced response to glibenclamide. The IC50 of glibenclamide to block KATP channels in FDB fibers was 1.3 ± 0.2 × 10−7 M in WT and 1.2 ± 0.1 × 10−6 M in Kir6.1wt/VM mice, respectively; and it was 1.2 ± 0.4 × 10−7 M in SOL WT fibers but not measurable in Kir6.1wt/VM fibers. The sensitivity of the KATP channel to MgATP was not modified in Kir6.1wt/VM fibers. Histopathological/immunohistochemical analysis of SOL revealed degeneration plus regressive-necrotic lesions with regeneration, and up-regulation of Atrogin-1, MuRF1, and BNIP3 mRNA/proteins in Kir6.1wt/VM mice. Kir6.1wt/VM mutation in skeletal muscle leads to changes of the KATP channel response to glibenclamide in FDB and SOL fibers, and it is associated with histopathological and gene expression changes in slow-twitch muscle, suggesting marked atrophy and autophagy.